2014
DOI: 10.1353/aad.2014.0024
|View full text |Cite
|
Sign up to set email alerts
|

Using Scaffolded Self-Editing to Improve the Writing of Signing Adolescent Deaf Students

Abstract: H E AU T H O R S investigated the impact of the Deaf StudentEditing Rubric (DSER) as a self-editing tool on the writing performance of prelingually profoundly deaf adolescent students whose first language is American Sign Language. The DSER was developed by the first author. The study participants included 15 Deaf students in 4 classrooms in grades 7-12. Writing samples were analyzed for all students, and the level of rubric use was assessed. Eight of the students were interviewed about their use of the DSER. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…First, using visual scaffolds with DHH students during shared and guided writing activities has led to improvements in students’ use of adjectives (Easterbrooks & Stoner, 2006). Second, rubrics have empowered DHH students to recognize specific writing traits to incorporate, particularly when metacognitively reflecting with one another in follow-up conversations (Appanah & Hoffman, 2014). Third, Kluwin and Kelly (1992) found that when teachers frequently engaged DHH students in the writing process, their writing and grammar improved.…”
Section: Secondary Writing Instruction With Dhh Studentsmentioning
confidence: 99%
“…First, using visual scaffolds with DHH students during shared and guided writing activities has led to improvements in students’ use of adjectives (Easterbrooks & Stoner, 2006). Second, rubrics have empowered DHH students to recognize specific writing traits to incorporate, particularly when metacognitively reflecting with one another in follow-up conversations (Appanah & Hoffman, 2014). Third, Kluwin and Kelly (1992) found that when teachers frequently engaged DHH students in the writing process, their writing and grammar improved.…”
Section: Secondary Writing Instruction With Dhh Studentsmentioning
confidence: 99%